Targeting ultra-poor households in Honduras and Peru - Dean Karlan; Bram Thuysbaert (Yale University, Economic Growth Center, 2013)
For policy purposes, it is important to understand the relative efficacy of various methods to target the poor. Recently, participatory methods have received particular attention. We examine the effectiveness of a hybrid two-step process that combines a participatory wealth ranking and a verification household survey, relative to two proxy means tests (the Progress out of Poverty Index and a housing index), in Honduras and Peru. The methods we examine perform similarly to one another by various metrics. They all target most accurately in the cases of the poorest and the wealthiest households but perform with mixed results among households in the middle of the distribution. Ultimately, given similar performance, the analysis suggests that costs should be the driving consideration in choosing across methods.
Keywords: C81; O12; O20; 330; poverty targeting; participatory wealth rankings; proxy means tests; Armutsbekämpfung; Zielgruppe; Wirkungsanalyse; Honduras; Peru